Identification of di-2-ethylhexyl terephthalate (DEHTP) metabolites using human liver microsomes for biomonitoring applications. Issue 4 (June 2015) - Silva, Manori J.; Samandar, Ella; Calafat, Antonia M.; Ye, Xiaoyun
Highlights We investigated the in vitro metabolism of di-2-ethylhexyl terephthalate (DEHTP) using human liver microsomes. We identified metabolites of DEHTP using mass spectrometry. DEHTP specific metabolites are suitable as biomarkers for human exposure assessment of DEHTP.